Intelligent Wearable Technology For Hajj: AI-Powered Smart Bracelet for Real-Time Pilgrim Management - Rosalina Rosalina; Hasanul Fahmi; Noor Lees Binti Ismail; Danny Ngo Lung Yao (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
The Hajj pilgrimage gathers millions of people each year, creating a dynamic environment that demands efficient health monitoring, safety management, and real-time coordination. This paper presents an AI-powered smart bracelet designed to enhance pilgrim management through the integration of Internet of Things (IoT) technology, fuzzy logic intelligence, and cloud computing. The wearable continuously collects physiological and environmental data—such as temperature, heart rate, humidity, and location—and processes them through a hybrid edge–cloud framework to ensure low latency and scalability. Artificial intelligence algorithms analyze sensor data to detect anomalies and issue early alerts during health or safety incidents. Experimental evaluation under simulated Hajj conditions achieved an average classification accuracy of 94.8%, data transmission latency below 3.5 seconds, and battery endurance of up to 20 hours. These results confirm the system’s reliability, energy efficiency, and suitability for large-scale real-time monitoring. The proposed framework contributes to safer and smarter Hajj operations by improving early risk detection, communication efficiency, and emergency response coordination.